Advances in Microwave‐Enhanced Chemical Vapor Deposition for Graphene Synthesis. Issue 18 (9th May 2022) - Wang, Hui; Han, Yuxiang; Luo, Pan; Zhou, Yanping; Chen, Qian; Zhu, Huacheng; Yang, Yang; Zhang, Bing; Huang, Kama
Abstract: Graphene has received intensive research interest in various areas due to its outstanding mechanical, electrical properties, high specific surface area and 2D flexible structure. Mechanical exfoliation generates defect‐free graphene, but suffers from ultra‐low yield. This drawback can be partially overcome by chemical vapor deposition method (CVD). However, conventional CVD imposes high temperature. In recent years, microwave plasma‐enhanced CVD (MPCVD) has been widely investigated as a viable strategy toward large‐area graphene synthesis. In this review, important issues during the process are summarized. Firstly, various MPCVD devices that have been explored for graphene synthesis are presented. Secondly, effect of carbon sources, nitrogen‐containing gases, and CO2 in the precursors are discussed. Thirdly, MPCVD enabled direct synthesis of graphene on metal substrates and non‐metal sustrates is discussed. Finally, the advances of MPCVD in lowering the graphene synthesis temperature are demonstrated. Abstract : In this review, important issues in graphene synthesis by microwave plasma‐enhanced chemical vapor deposition (MPCVD) are summarized. Firstly, various MPCVD devices that have been explored for graphene synthesis are presented. Secondly, effect of carbon sources and nitrogen‐containing gases in the precursors are discussed. Thirdly, MPCVD enabled direct synthesis of graphene on metal substrates and non‐metal sustrates is discussed. Finally, the advances of MPCVD in lowering the graphene synthesis temperature are demonstrated.